The inferno - Alighieri, Dante 1265-1321; Ciardi, John 1916-1986; MacAllister, Archibald T.; Cifelli, Edward M. (New York, New York New American Library, 2009)
In the first part of Dante's epic poem about the three realms of the Christian afterlife, a spiritual pilgrim is led by Virgil through the nine circles of Hell.
"Signet Classics."
Includes bibliographical references.
Keywords: Helly -- Poetry; Poetry, Medieval; Religious poetry